External fixation versus intramedullary nailing for the treatment of open tibial shaft fractures: A meta-analysis of randomized controlled trials - Zhao Chen; Rong Luo; Fei Xing; Zhou Xiang (Health Sciences Review, 2024)
The aim of this study is to compare external fixation versus intramedullary (IM) nailing to determine which strategy was more suitable for patients with open tibial shaft fractures. Eleven RCTs that compared the therapeutic outcomes between external fixation and IM nailing in patients suffering from open tibial shaft fractures were screened out from the PubMed, Embase, and Cochrane Library in this analysis. For open tibia fractures of Gustilo-Anderson I-IIIA, significantly lower incidence of malunion and superficial infection was revealed for the IM nailing group when compared with the external fixation group. Further subgroup analyses within I-IIIA fractures showed comparable results between fractures managed with IM nails and ring external fixators. In conclusion, IM nailing is recommended over external fixation for open tibia fractures of I-IIIA. In addition, the use of ring external fixators may be more suitable than the ordinary external fixators for the treatment of I-IIIA fractures.